2014
DOI: 10.1039/c3cs60282f
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in heterogeneous selective oxidation catalysis for sustainable chemistry

Abstract: Oxidation catalysis not only plays a crucial role in the current chemical industry for the production of key intermediates such as alcohols, epoxides, aldehydes, ketones and organic acids, but also will contribute to the establishment of novel green and sustainable chemical processes. This review is devoted to dealing with selective oxidation reactions, which are important from the viewpoint of green and sustainable chemistry and still remain challenging. Actually, some well-known highly challenging chemical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
405
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 714 publications
(413 citation statements)
references
References 339 publications
(688 reference statements)
4
405
0
4
Order By: Relevance
“…This approach has been applied to wood pulp delignification, in which oxidation of the C a alcohol to a ketone favours the breakdown of b-O-4 linkages. Wang et al [85] also reported a bifunctional Pd/CeO 2 catalyst able to efficiently cleave b-O-4 bonds in the presence of C a -hydroxyl group, in which synergy between palladium activation of the oxidant and the redox properties of ceria facilitates b-O-4 cleavage; Pd is widely used in heterogeneous catalysis for aerobic alcohol oxidation [86][87][88][89][90]. This bifunctional catalyst was able to transform a range of Organosolv lignin in ethanol under oxygen to vanillin, guaiacol, and 4-hydroxybenzaldehyde.…”
Section: Oxidative Transformationsmentioning
confidence: 99%
“…This approach has been applied to wood pulp delignification, in which oxidation of the C a alcohol to a ketone favours the breakdown of b-O-4 linkages. Wang et al [85] also reported a bifunctional Pd/CeO 2 catalyst able to efficiently cleave b-O-4 bonds in the presence of C a -hydroxyl group, in which synergy between palladium activation of the oxidant and the redox properties of ceria facilitates b-O-4 cleavage; Pd is widely used in heterogeneous catalysis for aerobic alcohol oxidation [86][87][88][89][90]. This bifunctional catalyst was able to transform a range of Organosolv lignin in ethanol under oxygen to vanillin, guaiacol, and 4-hydroxybenzaldehyde.…”
Section: Oxidative Transformationsmentioning
confidence: 99%
“…The design of heterogeneous oxidation catalysts by the molecular control of the active species and their uniform distribution into a controlled environment might allow finetuning of the catalytic features in order to improve the reactivity, selectivity and potential applications [1]. By analogy with naturally occurring Fe-or Cu-containing metalloenzymes, both the structure of the metal sites and the environment of their vicinities must be controlled [2].…”
Section: Introductionmentioning
confidence: 99%
“…One of the strategies in the C-H bond activation is the catalytic oxidation process. Oxidation process is one of the most viable, easy and efficient methods in VOC abatement and utilization technologies [95]. One of the commercially applied conversion technology is the catalytic methane combustion (CMC) (in the form of LNG and/or CNG) in automotive applications.…”
Section: From Methane To Chemicalsmentioning
confidence: 99%